Analisis Semiotika pada Strategi Persuasif Iklan Judi Online di Youtube Channel PlayOjo - Amin, Nur Izatul; Talani, Noval Sufriyanto; Mursalim, Muhammad Akram (Jambura Jurnal Ilmu Komunikasi, 2025)
The development of digital technology has driven a significant transformation in the advertising world, including the promotion of online gambling advertisements. This advertisements not only convey product but also construct certain meanings and myths thats influence how audiences perceive gambling practices. The research gap addresses in the research is the lack of semiotic analysis that specifically explores symbols and persuasive strategies. This research aims to analyze the visual symbols, persuasive meanings, and strategies used in online gambling advertisements on the PlayOJO YouTube channel. This research employs a qualitative approach using Roland Baerthes’ semiotic analysis, which includes the identification of sign, denotative meaning, connotative meaning, and myth formation. The results indicate that PlayOJO advertisements utilize symbols such as bright lights, joyful character expressions, vibrant colors, and narratives of winning to construct the myth that online gambling is a pleasurable activity that can bring luck and happines. These advertisements instill the idea that online gambling is a quick and enjoyable path to happines. In conclusion, the persuasive strategy in these advertisements operates subtly trough the peripheral route, emphasizing visual and emotional impression rather than logical argumentation. The implications of this research highlight the need for critical awareness of digital advertising messages that can influence attitudes and behaviors, as well as the urgency for stricter regulation of gambling advertisements on social media platforms.